The truth matters : a citizen's guide to separating facts from lies and stopping fake news in its tracks - Bartlett, Bruce R., 1951- (Ten Speed Press, 2017)
The media and political landscapes are littered with untrustworthy sources and the dangerous concept of "fake news." Bartlett helps you fight this deeply troubling trend and ensure that truth is not a permanent casualty. He presents actionable tips and tricks for reading critically, judging sources, using fact-checking sites, avoiding confirmation bias, identifying trustworthy experts, and more.